2012
DOI: 10.2337/dc11-1313
|View full text |Cite
|
Sign up to set email alerts
|

Mortality After Incident Cancer in People With and Without Type 2 Diabetes

Abstract: OBJECTIVEType 2 diabetes is associated with an increased risk of several types of cancer and with reduced survival after cancer diagnosis. We examined the hypotheses that survival after a diagnosis of solid-tumor cancer is reduced in those with diabetes when compared with those without diabetes, and that treatment with metformin influences survival after cancer diagnosis.RESEARCH DESIGN AND METHODSData were obtained from >350 U.K. primary care practices in a retrospective cohort study. All individuals with or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
368
2
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 383 publications
(397 citation statements)
references
References 16 publications
17
368
2
4
Order By: Relevance
“…Inconsistent with our findings, two previous studies reported significant reductions in all-cause mortality in users of metformin before [13] or after [14] lung cancer diagnosis. A further study reported a shorter overall survival in pre-diagnostic metformin users compared to non-users [12].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Inconsistent with our findings, two previous studies reported significant reductions in all-cause mortality in users of metformin before [13] or after [14] lung cancer diagnosis. A further study reported a shorter overall survival in pre-diagnostic metformin users compared to non-users [12].…”
Section: Discussionsupporting
confidence: 88%
“…A further study reported a shorter overall survival in pre-diagnostic metformin users compared to non-users [12]. Unlike our investigation, previous studies did not investigate dosedependent relationships [12][13][14] and metformin use after diagnosis was time-fixed [14], thus potentially introducing immortal time bias. Moreover, results from studies investigating allcause mortality could be reflective of non-cancer mortality.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Insulin resistance and hyperinsulinemia are the cornerstone of metabolic syndrome and are also factors for some cancers. The correlation between obesity and increased bladder cancer or bladder recurrence risk need further research to better clarify the potential mechanism (Eckel 2007;Borena et al, 2011;Currie et al, 2012;Lee et al, 2012;Liu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating epidemiologic evidence suggests that type 2 diabetes mellitus (T2DM) and/or certain diabetes treatments may be associated with prevalence, progression, or prognosis of some malignancies, but the risk may vary according to diabetes therapy and cancer site (Barone et al, 2008;Currie et al, 2012;Wang et al, 2013). For example, the cohorts of patients with T2DM were reported to have increased prevalence in several types of malignancies, such as liver, colorectal, pancreas, endometrial and breast cancers, etc (He et al, 2010;Wang et al, 2012;Elena et al, 2013;Zhang et al, 2013), and the all-cause mortality in patients with preexisting T2DM (preDM) was also increased in those with breast, prostate, pancreas and colorectal cancer, etc (Arif, et al, 2011;Currie et al, 2012;Hwang et al, 2013;Walker et al, 2013). Non-small-cell lung cancer (NSCLC) is the leading cause of cancer-related deaths worldwide (Siegel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%